INFLUENCE OF THE SOCIO-SPIRITUAL ENVIRONMENT IN THE FAMILY ON EDUCATION OF CHILDREN (Scientific journal of the Fergana State University, 2024)
In this article, it is justified that the family is a fortress that ensures human happiness, and it is explained that it has both divine and human protection. The family has continued since the creation of the human race and has been considered one of the main and honorable values of people in all periods of human history, in any system and conditions. The world of the family is a complex space in which a number of spiritual, moral, social, economic and political relations are embodied. Family well-being is the basis of national well-being. If we look at the history of our nation, it is revealed that all human qualities such as honesty, truthfulness, honor, shame, kindness, hard work are formed in the family. In this study, the role and position of the father in the family is explained. In the course of the research, a systematic analysis, a questionnaire survey on the topic "Influence of the socio-spiritual environment in the family on child upbringing" was conducted, and the conclusions obtained are presented in this article.In the family, a child is influenced to become either a perfect person or a selfish person. Even today we can see that the importance of these words of wisdom has not lost its power. Especially in today's era of globalisation, it is concluded that the importance of spiritual and educational propaganda in protecting our children from various ideological encroachments, in increasing their sense of ownership of events around them, and in combating encroachments that may endanger our peaceful life, our centuries-old spirituality and national values, is growing day by day.